Female College Students’ Thoughts Regarding Childbearing, Family, and Parenting Practices - Knuth, Madigan; Leibham, Mary Beth (My University, 2019)
Given the influx of information via technology (e.g., internet, social media) over the last 25 years, it is likely that current millennial college students are aware of various childbirth options (e.g., hospital birth, home birth), and more knowledgeable about the benefits of breastfeeding and vaccinations than students were 25 years ago. Further, exposure to information via technology has also likely increased college students' awareness of the variability in family structure (e.g., cohabitation, marriage). Within the field of Maternal & Child Health, it is essential for practitioners to be proactive in planning for future needs and addressing misconceptions. In doing so, it is likely that both maternal and child health outcomes will continue to improve in subsequent years. This study examined the variability in current UWEC female students' reported aspirations and knowledge surrounding childbearing, family structure, and parenting practices, particularly those practices that may have been less common 25 years ago (e.g., cohabitation, water births).
Color poster with text and graphs.
Keywords: Female college students; Family roles; Parenting; Posters